Digital Social Media, Youth, and Nonmedical Use of Prescription Drugs: The Need for Reform - Mackey, Tim K; Liang, Bryan A; Strathdee, Steffanie A (JMIR Publications, 2013)
The tragic death of 18-year-old Ryan Haight highlighted the ethical, public health, and youth patient safety concerns posed by illicit online nonmedical use of prescription drugs (NUPM) sourcing, leading to a federal law in an effort to address this concern. Yet despite the tragedy and resulting law, the NUPM epidemic in the United States has continued to escalate and represents a dangerous and growing trend among youth and adolescents. A critical point of access associated with youth NUPM is the Internet. Internet use among this vulnerable patient group is ubiquitous and includes new, emerging, and rapidly developing technologies-particularly social media networking (eg, Facebook and Twitter). These unregulated technologies may pose a potential risk for enabling youth NUPM behavior. In order to address limitations of current regulations and promote online safety, we advocate for legislative reform to specifically address NUPM promotion via social media and other new online platforms. Using more comprehensive and modernized federal legislation that anticipates future online developments is critical in substantively addressing youth NUPM behavior occurring through the Internet.